Usulan Pengurangan Jumlah Cacat Part Produk Frame X - Muhammad Musafak; Johan K. Runtuk; Sumartono Sumartono (President University, 2019)
Quality has an important role in a company. A defect product can The customer complaint of PT XYZ keep increasing in November 2017 in amount of 13.178 pcs. The highest defect occurred on frame X and visual problem. After analyzing using fishbone diagram, the cause of highest defect is caused by method and material.